Homodinuclear Lanthanide Complexes with the Divergent Heterotopic 4, 4′‐Bipyridine N‐Oxide (bipyMO) Ligand. Issue 40 (16th October 2018) - Armelao, Lidia; Belli Dell'Amico, Daniela; Bellucci, Luca; Bottaro, Gregorio; Ciattini, Samuele; Labella, Luca; Manfroni, Giacomo; Marchetti, Fabio; Mattei, Carlo Andrea; Samaritani, Simona
Abstract : The synthesis of dinuclear molecular complexes [Eu2 (dbm)6 (bipyMO)2 ], 1, [Tb2 (dbm)6 (bipyMO)2 ], 2, [Eu2 (tta)6 (bipyMO)2 ], 3 [Eu2 (hfac)6 (bipyMO)3 ], 4, [Tb2 (hfac)6 (bipyMO)3 ], 5 is here reported (bipyMO = 4, 4′‐bipyridine N‐oxide, Hdbm = dibenzoylmethane, Htta = thenoyltrifluoroacetone, Hhfac = hexafluoroacetylacetone). The products were obtained in mild conditions and with high yields reacting anhydrous lanthanide β‐diketonates and bipyMO in 1:1 or 1.5 molar ratio in toluene. X‐ray single crystal studies on2, 3, 4 showed that the heterotopic ligands are hypodentate, bridging the two lanthanide centres exclusively through the oxygen atom. Photoluminescence studies show bright red emissions from europium derivatives with absolute quantum yields up to 44 %. Abstract : The heterotopic divergent bipyMO ligand reacts with neutral diketonato lanthanide complexes to yield dinuclear compounds [Ln2 (β‐dik)6 (bipyMO) n ] (Ln = Eu, Tb) with a pendant nitrogen donor functionality. All the reported complexes have good emission properties with PLQY value up to 44 %. These derivatives are potentially useful as building blocks for the synthesis of heterometallic compounds.